Intellectual Property Rights in Pharmacy: Patent Laws and Their Impact on Drug Accessibility - Bhat, Qaisar Farooq; Ali, Mr. Md. Zulphakar (Journal of Science in Medicine and Life, 2025)
Property Rights as delineated within Intellectual Property Rights (IPR) constitute a pivotal component of the pharmaceutical sector, designed to foster innovation while concurrently presenting obstacles to the accessibility of medications. Patent legislation endows pharmaceutical enterprises with exclusive rights about novel pharmaceuticals for a predetermined duration, generally encompassing 20 years, thereby facilitating the recuperation of investments in research and development. Nevertheless, this monopolistic control often escalates drug prices, consequently delaying the emergence of affordable generic substitutes. This study investigates the ramifications of patent legislation on the accessibility of pharmaceuticals, with a particular emphasis on low and middle-income nations where exorbitant costs impede access to vital medicines. Within the pharmacy field, the principal facets of patent legislation encompass patent exclusivity, compulsory licensing, ever-greening, patent linkage, and data exclusivity. While patents catalyze innovation, they simultaneously erect considerable obstacles for patients requiring assistance. Amending patent legislation to curb ever-greening practices and ensuring transparency in the patenting framework can significantly alleviate monopolistic tendencies. A judicious approach is imperative to harmonize pharmaceutical innovation with the exigencies of global health. Policymakers are urged to enact regulations that facilitate equitable access to vital medicines. Through the implementation of strategic legal reforms, fostering international partnerships, and adopting ethical pricing strategies, it is feasible to construct an equitable and sustainable pharmaceutical environment that serves the interests of both innovators and patients globally.